2016
DOI: 10.1016/j.athoracsur.2016.01.109
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation Versus Surgical Aortic Valve Replacement for Severe Aortic Stenosis in Patients With Chronic Kidney Disease Stages 3b to 5

Abstract: CKD stages 3b to 5 increases the risk of mortality after TAVI and SAVR. In this subset of patients, SAVR was associated with somewhat better early and late survival. The risk of acute kidney injury was higher after SAVR. These findings suggest that CKD stages 3b to 5 does not contraindicate SAVR. Strategies to prevent severe acute kidney injury should be implemented with either SAVR or TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…Several observational studies and retrospective analysis of landmark trials have shown that TAVR has lower mortality, less acute kidney injury, and shorter length of hospital stay when compared to surgical aortic valve replacement (SAVR) in the high‐risk patients with CKD in the short‐term follow‐up . Nguyen and associates showed an advantage of TAVR in patients with an eGFR less than 60 mL/min/1.73 m 2 and observed that TAVR has excellent outcomes at 5‐years and renal failure is not predictive of adverse outcomes when compared to SAVR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies and retrospective analysis of landmark trials have shown that TAVR has lower mortality, less acute kidney injury, and shorter length of hospital stay when compared to surgical aortic valve replacement (SAVR) in the high‐risk patients with CKD in the short‐term follow‐up . Nguyen and associates showed an advantage of TAVR in patients with an eGFR less than 60 mL/min/1.73 m 2 and observed that TAVR has excellent outcomes at 5‐years and renal failure is not predictive of adverse outcomes when compared to SAVR.…”
mentioning
confidence: 99%
“…This study concludes that when the operative risk is not prohibitive, SAVR is an excellent choice in patients with advanced kidney disease. As these were not prospective randomized studies, they were only hypothesis generating rather than a proof …”
mentioning
confidence: 99%
“…Our search identified 14 observational comparative studies of TAVI versus SAVR using a propensity‐score analysis and reporting ≥3‐year all‐cause mortality, which enrolled a total of 4,197 patients (Tables and ). A study by D'Errigo et al exclusively included patients with chronic kidney disease stages of 3b to 5. A study by Rosato et al exclusively enrolled low‐risk patients with EuroSCORE II of <4%.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies, 6 studies , 6 studies , and 2 studies indicated, respectively, a statistically significant benefit , a statistically nonsignificant benefit , and a statistically nonsignificant disadvantage of SAVR over TAVI for ≥3‐year mortality. A pooled analysis of all the 14 studies demonstrated a statistically significant 54% increase in mortality with TAVI relative to SAVR (primary meta‐analysis; HR, 1.54; 95% CI, 1.31–1.81; P for effect < 0.00001; P for heterogeneity = 0.14; I 2 = 30%; Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation